Analisis Kinerja DPKAD Dalam Pengelolaan Pajak Hotel Guna Meningkatkan Kontribusi Terhadap Pendapatan Asli Daerah Kota Semarang - Fandi Ardiansyah; Kushandayani .; Purwoko . (Journal of Politic and Government Studies, 2015)
AbstractThe hotel tax is one source of income region has considerable potential .The management of the potential of the hotel tax will certainly impact on a good contribution to local revenue itself .Business growth rapidly in the city hotel of semarang supposed to be opportunities for enhancing local income tax sector in the city of semarang .It is certainly demanding more from Dinas Pengelolaan Keuangan dan Aset Daerah can dig in and keep potential of semarang city hotel tax .This study using methods descriptive quantitative .And the data via documentation and interview .The purpose of this research to find out the plan , processes and their performance as well as the driving force behind and inhibitors of in the implementation of the tax collection hotel in order to improve its contribution to the local revenue semarang city .Data obtained used to formulate recommendations as a form of an input in the sustainability of the election the hotel tax .Results in the field showed that, to be able to explore and recognize the potential as well as the need for taxpayers to provide hotel service and get maximum results in implementing the poll tax Dpkad semarang city faced with the decision-making process not in accordance with local regulation number 3year 2011 to maintain the existence of business hotels as a source of revenue . Despite the growth of tax revenue fluctuating hotel and not contribute greatly to the PAD but the result of the withdrawal of the last five years the hotel tax Semarang city fall into the category of highly effective.In an effort to improve performance in the implementation of tax withdrawal hotel in semarang city , recommendations that can be given is: government conducts updating data periodically to investigate potential and setting target every year .In the implementation of the management of the hotel tax it needs strict supervision , not only internally supervision or the employee performance , DPKAD also have to apply strict sanctions against prospective taxpayers who disobedient , the city government of semarang must also can create a business climate conducive , by means of improved security of semarang city economy so that business and tourism being increased so that many guests and tourists staying as well as utilizing hotel facilities and services inn in semarang city .The keywords: the management of the hotel tax, local revenue, performance